Participation of a Chosen Company in EU Tenders - Šatková, Jana (2007)
The thesis is focused on introduction of basic facts about EU tenders (who publish them, where they are published etc.) and elaborating a detailed project according to specifications of a particular EU tender in the field of translation industry to enable chosen company to succeed and pass really strict requirements and procedures EU bodies apply